Characteristics, causes and impact of headache among a sample of physicians working during COVID-19 pandemic - Sherien Farag; Ahmed ElSadek; Waleed Salah-Eldin; Shady Samy Georgy; Mai Fathy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background Headache is considered a common health problem affecting physicians during Coronavirus disease-19 (COVID-19) pandemic and has direct impact on their productivity. Wearing personal protective equipment (PPE), stress and lack of sleep are common factors affecting their headache. Results Out of 165 participants, 38(23%) experienced new onset headache. Participants using Combined Face and eye PPE usage were at higher risk of developing headache compared to single PPE users, Participants wearing face shield were at higher risk of developing headache compared to eyewear non users. Conclusion COVID-19 hospital’s physicians may experience new-onset headache or change in their previously existing headache, mostly disposed by PPE eyewear and combined face and eye PPE.